Identyfikacja ulic w siedemnasto- i osiemnastowiecznych księgach miejskich Pobiedzisk - Sieradzki, Andrzej (Poznańskie Spotkania Językoznawcze, 2015)
A description of manners of the identification of streets in manuscript documents, which the 17th and 18th centuries municipal year books were, is the subject of the article. Three types of phrases were analysed: the phrases with a sentence determiner, the phrases with a determiner in the form of the prepositional phrase and the phrases with a determiner in the form of adjective. The essential aim of the research is to establish possible semantic structures which were the semantic sources in the process of deriving the nominal groups that have become the street names. The results of the research are as follow: 1. streets were identified almost exclusively (apart from two cases) by deriving the semantic locative relation; 2. most of the locative relations were derived from the proper names taken from beyond the city area as in the case of the town of Gniezno; 3. in few nominal groups the locative relations were derived from the proper names that were in use in the city area as in the case of the town of Pobiedziska.